DEVELOPMENT OF TECHNICAL CREATIVITY OF GIFTED STUDENTS IN THE TEACHING OF TECHNOLOGICAL SUBJECTS BY AN INNOVATIVE APPROACH - M. Q. Muxliboyev (Bright Mind Publishing, 2026)
The patterns and trends in the integrative development of education, science, technology and production, the preparation of students for creative activity on the basis of technological education, the conceptual and scientific-methodological foundations of the problems of the development of technical creativity in them studied to one degree or another.